Quantity discrimination, decision-making, and the role of early-life conditions in a lizard - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Christopher R. Friesen; Amelia Y. Peardon; Daniel W. A. Noble (Evolutionary Ecology, 2026)
Quantity discrimination affects a range of behaviours essential for fitness, including social interactions, navigation, and foraging and is widespread across animal taxa. However, in reptiles, evidence for this ability — particularly for small number contrasts — remains limited and mixed. Early-life conditions, such as hormonal exposure and temperature, can also shape brain development and cognitive performance, potentially affecting numerical abilities. Here, we tested the ability of the common garden skink ( Lampropholis guichenoti ) to discriminate between quantities and the effects of elevated prenatal glucocorticoids and incubation temperature on quantity discrimination and decision-making. We assessed quantity discrimination using a spontaneous choice test with food as a stimulus. We subjected lizards to five two-choice tests differing in the number of items (1 VS 4, 1 VS 3, 2 VS 4, 2 VS 3, 3 VS 4) while controlling for total length and area. Contrary to our predictions, lizards did not show clear preferences toward the larger items, providing no evidence of spontaneous quantity discrimination in L. guichenoti . Furthermore, prenatal conditions did not influence latency to make a choice, also a proxy for decision-making. Despite these results, further investigation of quantity discrimination in live-prey-feeding reptiles and the impact of early conditions on other taxa remains an important area of research.

Isotopic (S-O-Sr) constraints on the evolution of the barite-polymetallic system in the Colipilli district, Neuquén Basin (Argentina) - Melisa A. Salvioli; María F. Lajoinie; Clemente Recio; Ana L. Rainoldi; Hernán G. de la Cal; Mabel E. Lanfranchini; Nora N. Cesaretti (Journal of South American Earth Sciences, 2026)

Application of error-corrected sequencing technologies for in vivo regulatory mutagenicity assessment - Carole L. Yauk; Anthony M. Lynch; Vasily N. Dobrovolsky; Maik Schuler; Stephanie L. Smith-Roe; Devon Fitzgerald; Jake Higgins; Naveed Honarvar; Frank Le Curieux; Shoji Matsumura; Sheroy Minocherhomji; Leslie Recio; et al. (Regulatory Toxicology and Pharmacology, 2026)

Early environmental conditions do not impact behavioural flexibility in an invasive and noninvasive lizard species - Pablo Recio; Dalton C. Leibold; Ondi L. Crino; Kristoffer H. Wild; Christopher R. Friesen; Basile Mauclaire; Amelia Y. Peardon; Daniel W.A. Noble (Animal Behaviour, 2025)

Revisiting the mercury cycle in marine sediments: A potential multifaceted role for Desulfobacterota - Blanca Rincón-Tomás; Anders Lanzén; Pablo Sánchez; Mónica Estupiñán; Isabel Sanz-Sáez; M. Elisabete Bilbao; Diana Rojo; Iñaki Mendibil; Carla Pérez-Cruz; Marta Ferri; Eric Capo; Ion L. Abad-Recio; et al. (Journal of Hazardous Materials, 2024)

Simultaneous analysis of seven 16S rRNA hypervariable gene regions increases efficiency in marine bacterial diversity detection - Kleopatra Leontidou; Ion L. Abad‐Recio; Verena Rubel; Sabine Filker; Martin Däumer; Alexander Thielen; Anders Lanzén; Thorsten Stoeck (Environmental Microbiology, 2023)
Environmental DNA sequencing is the gold standard to reveal microbial community structures. In most applications, a one‐fragment PCR approach is applied to amplify a taxonomic marker gene, usually a hypervariable region of the 16S rRNA gene. We used a new reverse complement (RC)‐PCR‐based assay that amplifies seven out of the nine hypervariable regions of the 16S rRNA gene, to interrogate bacterial communities in sediment samples collected from different coastal marine sites with an impact gradient. In parallel, we employed a traditional one‐fragment analysis of the hypervariable V3–V4 region to investigate whether the RC‐PCR reveals more of the ‘unseen’ diversity obtained by the one‐fragment approach. As a benchmark for the full deck of diversity, we subjected the samples to PCR‐free metagenomic sequencing. None of the two PCR‐based approaches recorded the full taxonomic repertoire obtained from the metagenomics datasets. However, the RC‐PCR approach detected 2.8 times more bacterial genera compared to the near‐saturation sequenced V3–V4 samples. RC‐PCR is an ideal compromise between the standard one‐fragment approach and metagenomics sequencing and may guide future environmental sequencing studies, in which bacterial diversity is a central subject.

Adopting duplex sequencing technology for genetic toxicity testing: A proof-of-concept mutagenesis experiment with N-ethyl-N-nitrosourea (ENU)-exposed rats - Stephanie L. Smith-Roe; Cheryl A. Hobbs; Victoria Hull; J. Todd Auman; Leslie Recio; Michael A. Streicker; Miriam V. Rivas; Gabriel A. Pratt; Fang Yin Lo; Jacob E. Higgins; Elizabeth K. Schmidt; Lindsey N. Williams; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

LP-57: Increasing Confidence in New Approach Methodologies for Inhalation Risk Assessment with Multiple End Point Assays Using 5-day RepeatExposure to 1,3-dichloropropene - I. Paudel; R. Barutcu; R. Samuel; M. Moreau; S. Slattery; J. Scaglione; L. Recio (Toxicology Letters, 2023)

Early microRNA responses in rodent liver mediated by furan exposure establish dose thresholds for later adverse outcomes - Gail M. Nelson; Gleta K. Carswell; Carol D. Swartz; Leslie Recio; Carole L. Yauk; Brian N. Chorley (Toxicology Letters, 2023)

Error-corrected duplex sequencing enables direct detection and quantification of mutations in human TK6 cells with strong inter-laboratory consistency - Eunnara Cho; Carol D. Swartz; Andrew Williams; Miriam V. Rivas; Leslie Recio; Kristine L. Witt; Elizabeth K. Schmidt; Jeffry Yaplee; Thomas H. Smith; Phu Van; Fang Yin Lo; Charles C. Valentine; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Effects of bisphenol F, bisphenol S, and bisphenol AF on cultured human osteoblasts - E. García-Recio; V. J. Costela-Ruiz; L. Melguizo-Rodríguez; J. Ramos-Torrecillas; R. Illescas-Montes; E. De Luna-Bertos; C. Ruiz (Archives of Toxicology, 2023)
Bisphenol A (BPA) analogs, like BPA, could have adverse effects on human health including bone health. The aim was to determine the effect of BPF, BPS and BPAF on the growth and differentiation of cultured human osteoblasts. Osteoblasts primary culture from bone chips harvested during routine dental work and treated with BPF, BPS, or BPAF for 24 h at doses of 10 –5 , 10 –6 , and 10 –7 M. Next, cell proliferation was studied, apoptosis induction, and alkaline phosphatase (ALP) activity. In addition, mineralization was evaluated at 7, 14, and 21 days of cell culture in an osteogenic medium supplemented with BP analog at the studied doses. BPS treatment inhibited proliferation in a dose-dependent manner at all three doses by inducing apoptosis; BPF exerted a significant inhibitory effect on cell proliferation at the highest dose alone by an increase of apoptosis; while BPAF had no effect on proliferation or cell viability. Cell differentiation was adversely affected by treatment with BPA analogs in a dose-dependent, observing a reduction in calcium nodule formation at 21 days. According to the results obtained, these BPA analogs could potentially pose a threat to bone health, depending on their concentration in the organism.

Coupling of cerebral blood flow and functional connectivity is decreased in healthy aging - Alvaro Galiano; Elisa Mengual; Reyes García de Eulate; Iñigo Galdeano; Marta Vidorreta; Miriam Recio; Mario Riverol; José L. Zubieta; María A. Fernández-Seara (Brain Imaging and Behavior, 2020)

Correlation between in vitro and in vivo data on food digestion. What can we predict with static in vitro digestion models? - T. Bohn; F. Carriere; L. Day; A. Deglaire; L. Egger; D. Freitas; M. Golding; S. Le Feunteun; A. Macierzanka; O. Menard; B. Miralles; A. Moscovici; et al. (Critical Reviews in Food Science and Nutrition, 2018)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

Adsorption of chromium(VI) onto electrochemically obtained magnetite nanoparticles - L. J. Martínez; A. Muñoz-Bonilla; E. Mazario; F. J. Recio; F. J. Palomares; P. Herrasti (International Journal of Environmental Science and Technology, 2015)

Longitudinal evaluation of hepatitis C viral persistence in HIV-infected patients with spontaneous hepatitis C clearance - A. Rivero-Juarez; A. Caruz; L. M. Real; L. Martinez-Dueñas; F. J. Marquez; M. Frias; E. Recio; A. Gordon; J. A. Pineda; A. Rivero; A. Camacho (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Understanding home range behaviour and resource selection of invasive common brushtail possums (Trichosurus vulpecula) in urban environments - A. L. Adams; M. R. Recio; B. C. Robertson; K. J. M. Dickinson; Y. van Heezik (Biological Invasions, 2013)

Analysis of parcel-based image classification methods for monitoring the activities of the Land Bank of Galicia (Spain) - T. Hermosilla; J. M. Díaz-Manso; L. A. Ruiz; J. A. Recio; A. Fernández-Sarría; P. Ferradáns-Nogueira (Applied Geomatics, 2012)

Trends in grass pollen season in southern Spain - Herminia García-Mozo; C. Galán; P. Alcázar; C. Díaz de la Guardia; D. Nieto-Lugilde; M. Recio; P. Hidalgo; F. Gónzalez-Minero; L. Ruiz; E. Domínguez-Vilches (Aerobiologia, 2010)